KUALITAS ORGANOLEPTIK SIRUP DAUN KELOR (Moringa oleifera) BERDASARKAN VARIASI KONSENTRASI GULA - Jenny Grice Telehala; H Sinay (Program Studi Pendidikan Biologi FKIP Unpatti, 2017)
Background: Moringa leaves are vegetables rich in nutrients, but rarely used by the community as a vegetable, because the aroma is sharp and bitter taste. Making Moringa leaf syrup can reduce the aroma sharp and bitter taste. Addition of sugar can affect the color, taste, aroma and viscosity of Moringa leaf syrup. Method: This study to measure organoleptic quality of Moringa leaf syrup using scoring method. Result: The result showed that the best color indicator was A0 treatment (70%), while the best taste, aroma and viscosity indicator was A3 (85%). Conclusion: There is influence of addition of sugar to organoleptic quality (color, flavor, aroma, viscosity) from Moringa leaf syrup. For color indicator with best criterion is treatment A0 (70%), while indicator of flavor, aroma and viscosity with best criterion is treatment of A3 (85%).